Transfer of Geoblasta pennicillata to Bipinnula (Chloraeinae, Orchidaceae) - Cisternas, Mauricio A.; Salazar, Gerardo A.; Verdugo, Gabriela (Phytotaxa, 2012)
The genus Bipinnula Comm. ex Jussieu (1789: 65) includes 11–12 species distributed in two disjunct areas of southern South America. One of these comprises southern Brazil, Uruguay, and eastern Argentina, where six species occur, and the other is Chile where the rest of the species are found (Gosewijn 1993, Pridgeon et al. 2003, Cisternas et al. 2012). Szlachetko & Margońska (2001), based on intuitive assessments of floral characters, speculated that Bipinnula ‘is polyphyletic and consists of two apparently unrelated groups, Bipinnula and Jouyella Szlachetko & Margónska (2001: 124). However, Jouyella is identical in circumscription to Bipinnula section Multiflorae Gosewijn (1993: 15) and we do not see the advantage of inflating nomenclature with further genera for which monophyly has not been formally tested. Therefore, we consider Jouyella as a synonym of Bipinnula.